A highly stable metal–organic framework with cubane-like clusters for the selective oxidation of aryl alkenes to aldehydes or ketones. Issue 26 (16th June 2021) - Liu, Teng; Shen, Xianfu; Shen, Xiang; He, Chixian; Liu, Jiaming; Liu, Jian-Jun
Abstract : A novel MOF with cubane-like clusters was prepared based on an electron-deficient triazine derivative, and it exhibits excellent thermal and chemical stability and can be used for the selective oxidation of aryl alkenes to aldehydes or ketones in mild conditions. Abstract : Triazine derivatives, a class of electron-deficient π-conjugated molecules with high photochemical activity and excellent luminescent characteristics, have been utilized as a kind of electron-acceptor for the construction of molecular cages, luminescent and photochromic materials. In this paper, a novel and highly stable MOF with cubane-like clusters, [Co4 (SO4 )3 (F)3 (tpt)2 (tatb)] (1 ) (tpt = 2, 4, 6-tris-(4-pyridyl)-1, 3, 5-triazine, H3 tatb = 4, 4′, 4′′-(1, 3, 5-triazine-2, 4, 6-triyl)tribenzoic acid), has been successfully synthesized based on a triazine derivative, and possesses unprecedented sulfate- and fluoride-bridged cubane-type tetranuclear cobalt clusters and a 3D + 3D → 3D open framework. Compound 1 shows a rather high BET surface area and exhibits excellent thermal stability and high chemical stability in common solvents and even in acidic or basic solutions (in a pH range from 4 to 12). Moreover, catalytic measurements show that compound 1 is an excellent heterogeneous catalyst for the selective oxidation of aryl alkenes to aldehydes or ketones with conversions of 97%.